Senja : Communal housing for tourists and seasonal workers in the fishing industry in the north of Norway - Eriksson, Anna (KTH, Arkitektur, 2018)
This project takes place in the north of Norway, on an Island called Senja. With its beautiful nature and reliable resource of fish it attracts tourists in the summer time and seasonal workers in the fishing industry during the winter. How can communal housing for tourists and workers act as a hub in the local community? Around this question a cluster of different functions has been developed that serves the whole community as well as the communal housing with private living units.